EU ABUNDANCES IN ACTIVE AND NON-ACTIVE STARS - Gorbaneva, T. I.; Mishenina, T. V. (Одеські астрономічні публікації, 2010)
Eu abundances have been determined for stars observed at high resolution, high signal to noise ratio with the ELODIE spectrograph at the 1.93- m telescope of the Observatoire de Haute Provence (France). Among them more than 30 stars are active stars with a fraction of BY Dra and RS CVn type stars for which spectral pecularities were investigated. For all stars fundamental parameters were determined earlier. We find the mean abundances of the majority of elements in active and non-active stars. Active and non active cool dwarfs show similar dependencies of elemental ratios vs [Fe/H].